The role of Curcuma longa essential oil in controlling acute toxoplasmosis by improving the immune system and reducing inflammation and oxidative stress - Ezzatkhah, Fatemeh; Mahmoudvand, Hossein; Raziani, Yosra (Frontiers in Cellular and Infection Microbiology, 2023)
Background Chemotherapy with synthetic drugs is the principal approach for toxoplasmosis treatment; however, recent studies reported the limitations and adverse side effects of these chemical drugs. Objective This study aimed to examine the in vitro and in vivo effects of Curcuma longa essential oil (CLE) against the Toxoplasma gondii RH strain. Methods The in vitro effect of different concentrations of CLE on T. gondii tachyzoites was assessed by cell viability assay. Flow cytometry and apoptosis analysis were performed, and nitric oxide production by CLE was also evaluated in tachyzoites. BALB/c mice were orally treated with various doses (1.25, 2.5, and 5 mg·kg−1·day−1) of CLE for 2 weeks. After the induction of acute toxoplasmosis in the mice, their survival rate and the mean number of peritoneal parasites were checked. The hepatic level of antioxidant enzymes and oxidative stress markers was evaluated by commercial kits. The mRNA expression level of proinflammatory cytokines such as interleukin 1-beta (IL-1β) and interferon-gamma (IFN-γ) was evaluated by quantitative real-time PCR. Results CLE, especially at 50 µg/ml, showed potent inhibitory effects on T. gondii tachyzoites. It increased the survival rate (ninth day) and reduced the mean number of peritoneal tachyzoites in the infected mice. CLE dependently increased (p < 0.01) the number of necrotic and apoptotic cells as well as NO production. CLE significantly (p < 0.05) reduced the hepatic level of oxidative stress markers but increased (p < 0.001) the antioxidant enzymes and proinflammatory cytokines in the infected mice, with no important toxicity for vital organs. Conclusion The findings of this survey revealed the significant in vitro inhibitory effects of CLE on T. gondii tachyzoites. The results also exhibited promising in vivo effects of CLE. CLE improved the survival rate of infected mice and reduced the parasite number in them. Although the mechanisms of action of CLE are not clear, our study demonstrated its beneficial effects on acute toxoplasmosis by strengthening the immune system and reducing inflammation and oxidative stress. Still, more studies are required to confirm these results.